The effect of the vaginal diaphragm and lubricant gel on acquisition of HSV-2. Issue 4 (29th March 2011) - de Bruyn, Guy; Shiboski, Stephen; van der Straten, Ariane; Blanchard, Kelly; Chipato, Tsungai; Ramjee, Gita; Montgomery, Elizabeth; Padian, Nancy
Abstract : Background: In the context of a multisite HIV prevention trial in Southern African women, we examined the effectiveness of the Ortho All-Flex Diaphragm, lubricant gel (Replens) and condoms compared to condoms alone on the incidence of herpes simplex virus type 2 (HSV-2) infections. Methods: We analysed data from 2016 sexually active women in Zimbabwe and South Africa. Women were followed quarterly, and specimens obtained at the closing visit from previously HSV-2 seronegative women were retested for HSV-2 antibodies using Focus HerpeSelect Elisa. The first visit at which the participant tested positive for HSV-2 was defined by back-testing. We compared the incidence of HSV-2 after randomisation between study arms in both intent-to-treat (ITT) and per-protocol populations. Results: 210 women acquired HSV-2 during study participation (HSV incidence: 6.8 cases/100 women years). Allocation to the intervention arm was found to offer no benefit in reduction of HSV-2 by modified ITT (HR 1.03, 95% CI 0.78 to 1.35; p=0.85) or per protocol analysis (HR 0.87, 95% CI 0.61 to 1.24; p=0.45). Conclusions: HSV-2 infection was common in the study population as detected by type-specific Elisa testing. Provision of diaphragm and lubricant gel offered no additional protection against HSV-2 acquisition over male condoms alone. Trial Registration: http://ClinicalTrials.gov ; number NCT00121459 .